Global Warming in Nepal: Challenges and Policy Imperatives - Chaudhary, Pashupati; Aryal, Kamal P (Journal of Forest and Livelihood, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Information on climate change is so far scattered and documents are written in technical language often obscured by sophisticated jargon and complicated mathematical models. As a result, information about the causes and consequences of climate change is not understood by the general public. The problem is particularly acute in developing countries such as Nepal where literature on climate change is insufficient to make firm conclusions and develop adaptation and mitigation measures. Hence, we attempt to summarize available information to develop a conceptual framework with a view to making it easily accessible among a wider audience. First, the impacts of global warming on ecological factors, ecosystem processes and functions, and also on human wellbeing are outlined in the global context. The issues are then discussed for Nepal using available evidence, models, and predictions supplemented by some primary data on local perception and knowledge. Finally, outlooks for future action, research and policy are discussed. Key words: climate change, global warming, ecosystems, human wellbeing, adaptation Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.4-13